Pengaruh “Five C”S Of Kredit Terhadap Pengambilan Keputusan Kredit Tanpa Agunan (KTA) - Meilany, Merry (Sharing: Journal of Islamic Economics Management and Business, 2024)
The aim of this research is to analyze the effect of applying the 5C principles on decision making for credit without collateral (KTA) at PT. BPR Anugerah Bintang Sejaterah Pekanbaru. This research uses a quantitative approach with data collection techniques, namely literature study, field study, interviews, observation, documentation and questionnaires. Meanwhile, the data analysis technique uses multiple regression analysis. A). Character (X1): With tcount 3.796 greater than ttable 2.65 with a significance level of 0.000 smaller than 0.05. So H0 is accepted and Ha is accepted, meaning that the Character variable influences credit decision making. B). Capacity (X2): With tcount -0.013 smaller than ttable 2.65 with a significance level of 0.990 greater than 0.05. So H0 is rejected and Ha is rejected, meaning that the Capacity variable has no effect on credit decision making. C). Capital (X3): With tcount 1.502 smaller than ttable 2.65 with a significance level of 0.139 greater than 0.05. So H0 is rejected and Ha is rejected, meaning that the Capital variable has no effect on credit decision making. D). Collateral (X4): With tcount -1.953 smaller than ttable 2.65 with a significance level of 0.056 greater than 0.05. So H0 is rejected and Ha is rejected, meaning that the Collateral variable has no effect on credit decision making. E). Condition (X5): With tcount 2.120 smaller than ttable 2.65 with a significance level of 0.038 smaller than 0.05. So H0 is rejected and Ha is accepted, meaning that the Condition variable has no effect on credit decision making.